Magnetic Resonance Imaging Applications on Infiltrative Cardiomyopathies. Issue 6 (November 2016) - Muehlberg, Fabian; Toepper, Agnieszka; Fritschi, Simone; Prothmann, Marcel; Schulz-Menger, Jeanette
Abstract : Infiltrative cardiomyopathies are a heterogenous group of diseases that typically lead to restrictive cardiac dysfunction. Due to similar phenotypes, accurate diagnosis is challenging without invasive endomyocardial biopsy which has historically been considered mandatory. Cardiac magnetic resonance (CMR) has been well established in the diagnostic workup of patients with suspected cardiomyopathies due to its unique capability for tissue differentiation and its unsurpassed accuracy in defining cardiac morphology and function. The increasing variety of CMR techniques has generated both excitement and uncertainty with regard to their potential clinical use and its role vis-à-vis conventional noninvasive imaging techniques. The purpose of this review is to give an overview of established and emerging CMR techniques and typical image characteristics of the most commonly encountered infiltrative cardiomyopathies.